Актуальні аспекти вмісту водню та кисню в алюмінієвих сплавах - Гнатуш, Віталій; Ворон, Михайло (Physico-technological Institute of Metals and Alloys, 2023)
The analysis of the scientific researches devoted to questions of influence of the content of hydrogen and oxide inclusions in aluminum alloys in the context of these impurities interaction of with various components of material is presented. Based on the published results of experiments in scientific works, aluminum alloys depending on their hydrogen content can be divided into the following four groups: aluminum alloys with nominal hydrogen content; aluminum alloys containing hydride-forming additives; aluminum alloys with high hydrogen content; aluminum alloys with excess hydrogen content (gas). Information on single- and multistage methods of aluminum melt refining, as well as classification of quality control methods for aluminum alloy refining is presented. Some features of properties of aluminum alloys which contain hydride-forming additives are considered. The results of the study of high hydrogen content on the mechanical characteristics of aluminum alloys are traced. Features of technologies of creation of aluminum alloys with ultrahigh content of gases (foam aluminum) are considered. Information on the content of non-metallic inclusions in aluminum and aluminum alloys and methods for determining their content in the melt is presented. Based on the review and analysis, the need for comprehensive studies of the system hydrogen – oxide – alloying/modifying metals in aluminum alloys is shown to clarify the mechanisms of physicochemical and metallophysical processes that are realized in the crystallization of aluminum melts. There is a need to use experimental planning to build mathematical models of the relationship between hydrogen/oxide content, process parameters and properties of samples and products made of aluminum alloys.